An Examination of Factors Determining User Privacy Perceptions of Voice-Based Assistants - Biodun Awojobi; Brett Landry (International School for Social and Business Studies, 2023)
Purpose: Voice-based assistants have become ubiquitous in our homes and all around us. We interact with voice-based assistants through smartphones, dedicated home devices, or other Internet-connected devices. The proliferation of these devices in our lives makes us question whether the data transmitted through these devices are secure and the role perception of privacy the users of these devices have in the usage of the device. This paper focuses on the user privacy issues specific to two voice-based assistants - Amazon Alexa and Google Assistant using quantitative and qualitative methods. The paper will answer three research questions regarding user privacy perceptions and how a user's technology adoption, smartphone operating system, and demographics influence their perception of privacy. Study design/methodology/approach: This is a mixed research study where survey data was collected from faculty, staff, and students of a large University in the United States and professional connections globally. Findings: Privacy perceptions vary based on user age, educational level, gender, smartphone adoption, and technical awareness and expertise. Originality/value: This study is unique in highlighting the perception of privacy for voice-based assistants and assigning a numerical value based on survey data to the concern. Another feature of the study is its correlation of privacy perception with mobile phone operating systems and the level of technical expertise of voice-based assistant users.